2020
DOI: 10.3390/polym12010183
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Amphiphilic Block-Copolymers Based on Synthetic Glycopolymer and Poly(Amino Acid) as Potential Drug Delivery Systems

Abstract: In this work, a method to prepare hybrid amphiphilic block copolymers consisting of biocompatible synthetic glycopolymer with non-degradable backbone and biodegradable poly(amino acid) (PAA) was developed. The glycopolymer, poly(2-deoxy-2-methacrylamido-D-glucose) (PMAG), was synthesized via reversible addition-fragmentation chain transfer (RAFT) polymerization. Two methods for modifying the terminal dithiobenzoate-group of PMAG was investigated to obtain the macroinitiator bearing a primary aliphatic amino gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…Levit et al also recently demonstrated that NPs consisting of biodegradable poly(amino acid) and poly(2-deoxy-2-methacrylamido-D-glucose) (PMAG) can function as a reliable delivery system for paclitaxel in glutathione-rich conditions [159]. Great results were achieved when evaluated in A549 (human lung carcinoma cells) and MCF-7 (human breast adenocarcinoma) cells.…”
Section: Thiomer-based Conjugates For Taxanes and Other Anticancer Api Administrationmentioning
confidence: 99%
“…Levit et al also recently demonstrated that NPs consisting of biodegradable poly(amino acid) and poly(2-deoxy-2-methacrylamido-D-glucose) (PMAG) can function as a reliable delivery system for paclitaxel in glutathione-rich conditions [159]. Great results were achieved when evaluated in A549 (human lung carcinoma cells) and MCF-7 (human breast adenocarcinoma) cells.…”
Section: Thiomer-based Conjugates For Taxanes and Other Anticancer Api Administrationmentioning
confidence: 99%
“…They can be fully biodegradable, such as poly(lactic acid) [ 14 ] or poly(L-amino acids) [ 8 ], or possess non-biodegradable carbon–carbon backbone bearing cleavable bio-inspired side units, such as saccharide fragments [ 15 ]. In order to increase the lifetime of delivery systems based on amphiphilic copolymers, the hybrid systems that combine biodegradable and non-biodegradable polymer fragments can be a matter of choice [ 16 , 17 ]. Currently, a number of amphiphilic hybrid and fully synthetic copolymers have been synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(ethylene glycol) (PEG), polyoxazolines, different polysaccharides, hydrophilic poly(amino acids), and synthetic glycopolymers are usually used as hydrophilic blocks, while aliphatic polyesters (poly(lactic acid) (PLA), polycaprolactone, etc. ), polycarbonates, hydrophobic poly(amino acids), polystyrene, poly(butyl methacrylate), etc., are utilized as hydrophobic blocks [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1–4 ] The increasing interest for amphiphilic copolymers as drug delivery carriers is mainly related to their characteristic self‐assembling tendency. [ 5,6 ] Amphiphilic copolymers can assemble spontaneously into highly ordered nanoscopic core–shell micelles. The hydrophobic segments of amphiphilic copolymer form the core region of the micelle, while the hydrophilic blocks form outer shell.…”
Section: Introductionmentioning
confidence: 99%